The Key Factors for the Fate and Transport of Petroleum Hydrocarbons in Soil With Related in/ex Situ Measurement Methods: An Overview - Wang, Liang; Cheng, Ying; Naidu, Ravi; Bowman, Mark (Frontiers in Environmental Science, 2021)
Once petroleum hydrocarbons (PHs) are released into the soil, the interaction between PHs and soil media is dependent not only upon the soil properties but also on the characteristics of PHs. In this study, the key factors influencing the interactions between PHs and soil media are discussed. The key factors include: 1) the characteristics of PHs, such as volatility and viscosity; and 2) soil properties, such as porosity, hydraulic properties and water status, and organic matter; and 3) atmospheric circumstances, such as humidity and temperature. These key factors can be measured either ex-situ using conventional laboratory methods, or in situ using portable or handheld instruments. This study overviews the current ex/in situ techniques for measuring the listed key factors for PH contaminated site assessments. It is a tendency to apply in situ methods for PH contaminated site characterisation. Furthermore, handheld/portable Fourier transform infrared spectroscopy (FTIR) instrument provides tremendous opportunities for in-field PH contaminated site assessment. This study also reviewed the non-destructive FTIR spectroscopy analysis coupling with handheld FTIR for in-field PH contaminated site characterisation, including determining the concentration of total PH, dominant PH fractions and soil key properties for PH transport modelling.